2022
DOI: 10.1038/s41598-022-20180-0
|View full text |Cite
|
Sign up to set email alerts
|

HSV-1 0∆NLS vaccine elicits a robust B lymphocyte response and preserves vision without HSV-1 glycoprotein M or thymidine kinase recognition

Abstract: Effective experimental prophylactic vaccines against viral pathogens such as herpes simplex virus type 1 (HSV-1) have been shown to protect the host through T and/or B lymphocyte-driven responses. Previously, we found a live-attenuated HSV-1 mutant, 0ΔNLS used as a prophylactic vaccine, provided significant protection against subsequent ocular HSV-1 challenge aligned with a robust neutralizing antibody response. Yet, how the virus mutant elicited the humoral immune response relative to parental virus was unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Understanding cellular responses following the administration of vaccines is crucial in assessing their efficacy and safety and in the development of improved vaccine strategies. Gmyrek et al 11 characterize the B cell response in mice vaccinated with a live-attenuated HSV-1 mutant, 0ΔNLS, and compare it to the parental virus, GFP105. The study found that 0ΔNLS vaccination resulted in a more robust B cell response, including an increase in CD4 + follicular helper T cells, germinal B cells, and class-switched B cells, as well as an elevated titer of HSV-1-specific antibody.…”
mentioning
confidence: 99%
“…Understanding cellular responses following the administration of vaccines is crucial in assessing their efficacy and safety and in the development of improved vaccine strategies. Gmyrek et al 11 characterize the B cell response in mice vaccinated with a live-attenuated HSV-1 mutant, 0ΔNLS, and compare it to the parental virus, GFP105. The study found that 0ΔNLS vaccination resulted in a more robust B cell response, including an increase in CD4 + follicular helper T cells, germinal B cells, and class-switched B cells, as well as an elevated titer of HSV-1-specific antibody.…”
mentioning
confidence: 99%